THE CHILDREN OF FOREIGN IMMIGRANTS AS A STUDY OBJECT OF SOCIOLOGY - García, Iñaki (ANDULI, Social Sciences Journal, 2004)
¿Why people who never immigrated are considered immigrants? ¿What do “second generation immigrants” have in common with “first generation immigrants”, and what makes the difference between them? This article deals with these questions, taking the expression “second generation” as a path for analyzing how Spanish society represents the children of immigrants, and making the point on its stigmatizing contents. Then, some remarks are made on the rise in Spain of sociological studies on children of immigrants, comparing this phenomenon with the case of France, and discussing two subjects those studies commonly deal with: culture and identity. Finally, the Foucauldian concept of bio-politics is taken as a key for understanding the problematical relationship, societies which receive immigration maintain with the population issued from it.